Histological Topographical Comparisons of Atherosclerosis Progression in Juveniles and Young Adults - Homma, Satoki (2007)
BACKGROUND: The histologically topographic comparisons on atherosclerosis progression among three anatomical sites, mid-thoracic and lower abdominal aorta and left anterior descending coronary artery (LAD) were performed using a young population (age 15-34) from the Pathobiological Determinants of Atherosclerosis in Youth (PDAY) study. METHODS AND RESULTS: The histological classification based on the American Heart Association grading scheme showed that in the thoracic aorta type 2 lesions (numerous macrophage foam cells with fine particles but no pools of extracellular lipid) appeared in the first ten year age group, with no significant change in prevalence in the next ten years. Lesions greater than type 2 were rarely seen in the thoracic aorta. Although type 2 lesions appeared later in the LAD than in the aorta, the lesions within the LAD progressed rapidly to more advanced lesions (types 4 and 5) or atheroma. Lesion development in the abdominal aorta was intermediate to lesion development in the thoracic aorta and the LAD. CONCLUSIONS: The most striking topographic difference on lesion progression among the three anatomical sites was the vulnerability of type 2 lesions to progress into advanced lesions. The histology study, including immunohistochemistry limited to the type 2 lesions suggested that lesion progression was related to the intimal thickness and the amount of collagen but not to the number of macrophage foam cells.